Contribution of the new economy to Estonia's economic growth and convergence with the European economy - Teet Rajasalu; Anton Laur (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
Contribution of the New Economy to Estonia's economic growth is studied from the aspects of information and communication technology (ICT) penetration and development of high and medium-high tech industries. Comparison with EU member states and other candidate countries reveals that especially Internet penetration in Estonia is rather high. Contribution of high tech exports is also good in international comparison. Nevertheless, the direct impact of high tech industries and especially medium-high tech industries on economic growth might have been better. The main impact on growth is indirect and goes via high ICT level in the economy as a whole.
Keywords: 330; Wirtschaftswachstum; Wissensgesellschaft; Informationstechnik; Hochtechnologie; Estland; EU-Staaten; New Economy